Phosphorescent Oxygen-Sensitive Probes - Papkovsky, Dmitri B.; Zhdanov, Alexander V.; Fercher, Andreas; Dmitriev, Ruslan I.; Hynes, James; SpringerLink (Online service) (Basel : Springer Basel : Imprint: Springer, 2012)
Biological O2 sensing probes and measurement techniques were first introduced in the late 80s. In the last 3-5 years they have undergone major development that have made them available and affordable for a broad range of applications in various disciplines of the life and biomedical sciences. These new chemistries and technologies, which are significantly different from the majority of other fluorescence-based probes and detection techniques, have already demonstrated their high utility. This book will provide a systematic overview of the existing and emerging O2 sensing technologies in their different modifications, a practical guide to their rational selection and use, and examples of biological applications/case studies, including details on how to set up and conduct such experiments, troubleshoot and interpret the data.
O2-sensitive probes based on phosphorescent metalloporphyrins -- O2 analysis on a fluorescence spectrometer or plate reader -- O2 Imaging in biological specimens.
Keywords: Medicine; Biochemical engineering; Cytology; Microbiology; Cytology -- Research_xMethodology.; Biomedical engineering; Biomedicine; Molecular Medicine; Biological Techniques; Biochemical Engineering; Cell Biology; Microbiology; Biomedical Engineering